ANALISIS ORGANOLEPTIK KUE BANGKIT MENGGUNAKAN TELUR BERBEDA - Sugiarti Sugiarti; Fitriani Fitriani; Raga Samudra (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
This research is to find out the response of the learner to the use of different types of eggs in the making of the typical rose cake martapura South Kalimantan. The study used an experimental method with a randomized block design (RAK) with 5 treatments and 4 replays. The treatment using egg types is different from the code (BB: buras eggs), (BR: race eggs), (BI: duck eggs) and (BP: quail eggs) where Group I uses duck eggs, Group 2 uses buras chicken eggs, Group 3 uses chicken eggs and Group 4 uses quail eggs. Observed variables include color, aroma, taste, and texture. Analyze the data using Anova and continue with Duncan's test. The results showed that the use of different types of eggs in the manufacture of rose cakes had no real effect (P> 0.05) on color, aroma, taste, and texture.